InSAR measurement of the deformation around Siling Co Lake: Inferences on the lower crust viscosity in central Tibet. Issue 7 (17th July 2015) - Doin, Marie‐Pierre; Twardzik, Cédric; Ducret, Gabriel; Lasserre, Cécile; Guillaso, Stéphane; Jianbao, Sun
Abstract The Siling Co Lake is the largest endorheic lake in Central Tibet. Altimetric measures, combined with lake contours, show that in 1972–1999 its water level remained stable, while it increased by about 1.0 m/yr in the period 2000–2006. The increased rate gradually stepped down to 0.2 m/yr in 2007–2011. The ground motion associated with the water load increase is studied by interferometric synthetic aperture radar (InSAR) using 107 ERS and Envisat SAR images during the period 1992–2011. The deformation amplitude closely follows the lake level temporal evolution, except that subsidence continues in 2008–2011, while the lake level stagnated. This temporal evolution suggests a non elastic relaxation process taking place at a decade timescale. Phase delay maps are used to constrain possible layered viscoelastic rheological models. An elastic model could partly explain the observed subsidence rate if elastic moduli are about twice lower than those extracted from VP/VS profiles. The surface deformation pattern is also extracted by projecting the phase delay maps against the best fit model temporal behavior. It shows that deep relaxation in the asthenosphere is negligible at the decade timescale and favors the existence of a ductile channel in the deep crust above a more rigid mantle. Overall, the best fit model includes a ductile lower crust, with a viscosity of 1–3 × 1018 Pa s between 25 and 35 km and the Moho (at 65 km), overlying a rigid mantle.